Sexual Precocity of Nellore Bulls that are Offspring of Super Precocious, Precocious and Normal Cows in Extensive Farming Conditions - Siqueira, J. B.; Oba, Eunice [UNESP]; Pinho, R. O.; Guimaraes, S. E. F.; Neto, T. M.; Guimaraes, J. D. (Wiley-Blackwell, 2014)
Contents The objective of this work was to verify that mothers classified as super precocious (M1) and precocious (M2) produce more precocious bulls than females classified as normal (M3). This study included 21186 animals with an average age of 21.29 +/- 1.77months that underwent a breeding soundness evaluation from 1999 to 2008. Of these animals, 2019, 6059 and 13108 were offspring of M1, M2 and M3 females, respectively. In the breeding soundness examination, the animals were classified as sound for reproduction, sound under a natural mating regime, unsound for reproduction and discarded. To compare the averages obtained for each category of mother within the individual breeding soundness classes, a chi-square test with a 5% error probability was used, considering the effects of year and month of birth and farm. For the three classes of mothers (M1, M2 and M3), 67.26, 67.22 and 64.16% of bull calves were considered sound for reproduction and 19.71, 19.46 and 21.90% were considered unsound for reproduction, respectively. There was no difference in the frequency of animals that were sound for reproduction under the natural breeding regime between the three classes of mothers (8.87, 9.31 and 9.19%, respectively). There was a difference between the numbers of precocious and normal females that were discarded, with frequencies of 4.01 and 4.75%, respectively (p<0.05). There were differences in year and month of birth and farm between super precocious and precocious cows in relation to the breeding soundness classification of the animals. It was concluded that the bull offspring of super precocious and precocious cows presented a higher percentage of approval in the breeding soundness examination than the bull offspring of normal cows, demonstrating that the selection for precocity of females has contributed to an increase in the sexual precocity of the herd in relation to the sexual maturity of bulls.